Analisis implementasi kebijakan kawasan tanpa rokok di lingkungan pendidikan - Natasya Zalta Amany; Andy Amir; Dwi Noerjoedianto; Asparian Asparian (Holistik Jurnal Kesehatan, 2026)
Background: The smoke-free zone policy is one of the government's efforts to create a healthy environment and protect the public from exposure to cigarette smoke, particularly in educational settings. Schools play a strategic role in preventing smoking among adolescents, as the number of new smokers continues to rise. However, the implementation of the smoke-free zone policy in schools is often suboptimal due to limited resources, lack of supervision, and the absence of clear operational guidelines. Purpose: To analyze the implementation of the smoke-free zone policy in educational settings. Method: This study used a qualitative descriptive design. This study was conducted at State Senior High School 5 in Jambi City, located at Simpang IV, Sipin Village, Telanaipura District, Jambi City, from March to April 2026. Informants included the principal, teachers, guidance counselors, students, security officers, and canteen vendors. Data collection was conducted through in-depth interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. Results: Policy implementation has not been optimal. Communication regarding the smoking ban has been implemented through regulations and socialization, but coordination with external parties remains limited. The resources, facilities, and infrastructure supporting the policy remain inadequate. Although the entire school community generally supports the policy, violations are still found due to low awareness and weak oversight. Furthermore, there is no organizational structure or specific standard operating procedures (SOPs) for smoke-free areas. Conclusion: The implementation of the smoke-free area policy still requires improvement, particularly in terms of supervision, provision of supporting facilities, and enforcement to create a healthy and smoke-free school environment. Suggestion: Future research should involve a larger sample size and location, and use quantitative or mixed methods to evaluate the effectiveness of the smoke-free area policy and identify factors influencing its successful implementation.   Keywords: Education System; Policy Implementation; Smoke-Free Area.